International law and the proliferation of weapons of mass destruction - Joyner, Daniel (Oxford : Oxford University Press, 2009)
This text analyses the international law and international organisations that have been constructed to regulate the worldwide proliferation of weapons technologies, particularly those that have been classified as weapons of mass destruction such as nuclear, chemical and biological weapons.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Weapons of mass destruction (International law); Nuclear nonproliferation; Nuclear weapons (International law); Nuclear fuels -- Law and legislation; Security, International; Deterrence (Strategy); Arms control